Peran Penting Software Quality Assurance Dalam Pengembangan Aplikasi - Respiar, Boby; Fernanda, Arif; Taryadi, Taryadi; Maulana, Fariz; Anshor, Abdul Halim (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
Software Quality Assurance (SQA) has an important role in application development, specifically to ensure quality, reliability, and end-user satisfaction. This study aims to explore the role of SQA in improving the quality of applications through the application of effective standards and testing methods. By implementing SQA, potential errors can be detected early, reducing the risk and costs that may occur due to software defects. This study uses a qualitative approach through literature studies and interviews with IT professionals to gain a deeper understanding of the impact of SQA on the development process. The results show that SQA not only improves the quality of the final product but also improves the efficiency of the development team. Therefore, the implementation of SQA should be an inseparable component in every stage of application development.